Karakteristik Pasien Dengan Penyakit Ginjal Kronis Stadium V Yang Menjalani Hemodialisis Reguler Di Rumah Sakit Tabanan - MASYENI, SRI; MADE , SUHITA GIANI; PUTU, ARYA SURYANDITHA (Hang Tuah Medical Journal, 2025)
Abstract Chronic Kidney Disease (CKD) significantly impacts global health, contributing to both morbidity and mortality. This condition is characterized by severe kidney damage, which results in increased blood urea levels and can lead to serious complications. Reports indicate that the number of CKD cases is on the rise. This study is descriptive and employs a cross-sectional design, analyzing the medical records of CKD patients. The focus is on individuals who underwent examinations at Tabanan Hospital between January 1, 2019, and May 31, 2024. A total of 101 subjects were selected for the analysis. The results revealed that the majority of patients with stage V chronic kidney failure were over 60 years old (38.6%). The highest incidence of CKD was observed in men, accounting for 53.5% of the cases. Most patients had hypertension that was managed with medication (67.3%), and approximately 50.5% of the subjects experienced severe anemia